2022
DOI: 10.1021/acs.estlett.2c00556
|View full text |Cite
|
Sign up to set email alerts
|

Weakened Gas-to-Particle Partitioning of Oxygenated Organic Molecules in Liquified Aerosol Particles

Abstract: Aqueous-phase chemistry plays an important role in secondary organic aerosol (SOA) formation. However, the mechanism of the interaction between aerosol physics and chemistry is still poorly understood. Here continuous measurements of the gas- and particle-phase composition of organics were conducted using an iodine-adduct time-of-flight chemical ionization mass spectrometer coupled with a filter inlet for gases and aerosols in Beijing to understand the physicochemical processes related to SOA formation. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, we observed that secondary transformation of SIA and SOA was significantly enhanced after phase transition with higher ALW mass during the observation. Our findings indicate that the secondary aerosol formation could be impeded on non-liquid particles due to limited mass transfer between gas and particle phase for relevant reaction components (Ravishankara, 1997;Shiraiwa et al, 2011;Abbatt et al, 2012;Ma et al, 2022), whereas it is facilitated in liquid particles. It is therefore recommended that non-liquid to liquid phase transition may be considered to be the kick-off for the positive feedback loops between ALW and secondary aerosol formation during haze events.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 85%
“…However, we observed that secondary transformation of SIA and SOA was significantly enhanced after phase transition with higher ALW mass during the observation. Our findings indicate that the secondary aerosol formation could be impeded on non-liquid particles due to limited mass transfer between gas and particle phase for relevant reaction components (Ravishankara, 1997;Shiraiwa et al, 2011;Abbatt et al, 2012;Ma et al, 2022), whereas it is facilitated in liquid particles. It is therefore recommended that non-liquid to liquid phase transition may be considered to be the kick-off for the positive feedback loops between ALW and secondary aerosol formation during haze events.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 85%
“…Continuous field observations from October 1, 2021, to September 31, 2022, were conducted at the Aerosols and Haze Laboratory (AHL) at Beijing University of Chemical Technology (AHL/BUCT, 39.94°N, 116.30°E, Figure S1). Detailed descriptions of this site have been provided elsewhere. , An I-LToF-CIMS was used to measure the Cl 2 and ClNO 2 levels. The Cl 2 measurements were calibrated with permeation tubes (KIN-TEC Corp.) exhibiting permeation rates of 250 ng min –1 .…”
Section: Methodsmentioning
confidence: 99%
“…Detailed descriptions of this site have been provided elsewhere. 33,34 An I-LToF-CIMS was used to measure the Cl 2 and ClNO 2 levels. The Cl 2 measurements were calibrated with permeation tubes (KIN-TEC Corp.) exhibiting permeation rates of 250 ng min −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The field measurements were performed at the west campus of Beijing University of Chemical Technology (BUCT, longitude 116.31°E and latitude 39.95°N). Detailed site descriptions have been recorded in previous studies (Liu et al., 2020; Ma et al., 2022; Yan et al., 2022). Briefly, BUCT is located in the western part of the Beijing metropolitan area (Figure S1 in Supporting Information ).…”
Section: Methodsmentioning
confidence: 99%